2022
DOI: 10.1155/2022/7122738
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Diet-Dependent Changes in Hepatic Lipidomic Profiles of Phospholipids in Male Mice: Age Acceleration in Cyp2b-Null Mice

Abstract: Increases in traditional serum lipid profiles are associated with obesity, cancer, and cardiovascular disease. Recent lipidomic analysis has indicated changes in serum lipidome profiles, especially in regard to specific phosphatidylcholines, associated with obesity. However, little work has evaluated murine hepatic liver lipidomic profiles nor compared these profiles across age, high-fat diet, or specific genotypes, in this case the lack of hepatic Cyp2b enzymes. In this study, the effects of age (9 months old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…On the other hand, different researchers described that the increased BMI factors had an directly proportionate connection with daily diet. 15,17 LDL cholesterol levels were found to be higher and HDL cholesterol levels to be lower in people with high BMI 5,7,13 . There was found to be no connection between gender and alterations in lipid profiles.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, different researchers described that the increased BMI factors had an directly proportionate connection with daily diet. 15,17 LDL cholesterol levels were found to be higher and HDL cholesterol levels to be lower in people with high BMI 5,7,13 . There was found to be no connection between gender and alterations in lipid profiles.…”
Section: Discussionmentioning
confidence: 93%
“…The distribution of dietary fatty acids appears to have a significant role in modulating the effects of carbohydrate restriction on LDL-C and HDL-C. 15,16 A quantitative meta-analysis of metabolic ward studies (395 dietary trials with a median duration of one month, among 129 groups of people) found that removing 60% of dietary cholesterol and substituting other fats for 60% of saturated fats would reduce total cholesterol (TC) by about 31 mg/dL, or 10-15% 10,12,16 , with LDL-C dropping by about 4/5 of this reduction. According to numerous research, increased fish diet is advised to increase intake of omega-3 fatty acids and to lower the risk of metabolic diseases 17,19 . No correlation between consumption of milk products and an elevated risk of CHD, stroke, or other heart and vascular illnesses was discovered in the observational study's findings, regardless of the amount of milk fat present.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that CYP2B6 has the ability to metabolize EtOH, but these studies did not further characterize how CYP2B6 regulates EtOH metabolism (Busby et al, 1999;Hamitouche et al, 2006;Vuppugalla et al, 2007) (Damiri & Baldwin, 2018;Heintz et al, 2019Heintz et al, , 2020Heintz et al, , 2022. In addition, studies using conditional P450 oxioreductase (POR) mice and Cyp2b-knockdown mice provided evidence that CYP2B enzymes are likely involved in unsaturated fatty acid metabolism (Damiri & Baldwin, 2018;Finn et al, 2009) mice.…”
Section: Discussionmentioning
confidence: 99%
“…While the increased EtOH concentrations in Cyp2b10 KO mice may contribute to the increased liver injury, CYP2B enzymes are known to play other physiological roles. Studies in Cyp2b ‐knockdown and null mice have shown that CYP2B enzymes have sexually dimorphic effects on lipid homeostasis, with male Cyp2b ‐knockdown/null mice gaining more weight on HFD (Damiri & Baldwin, 2018; Heintz et al, 2019, 2020, 2022). In addition, studies using conditional P450 oxioreductase (POR) mice and Cyp2b ‐knockdown mice provided evidence that CYP2B enzymes are likely involved in unsaturated fatty acid metabolism (Damiri & Baldwin, 2018; Finn et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Three recent studies found Cyp2b9 exhibited the highest increase in gene expression following a high-fat diet (HFD) in mice [ 8 10 ]. Our previously generated Cyp2b9/10/13-null (Cyp2b-null) mice are age- and diet-induced obese (DIO) with increased NAFLD in males [ 10 , 11 ]. Similarly, age-dependent lipid accumulation was observed in RNAi-mediated Cyp2b-knockdown male mice [ 12 ].…”
Section: Introductionmentioning
confidence: 99%